Electrochemical detection characteristics of the composite films of boron‐doped nanocrystalline diamond and amorphous carbon prepared using the coaxial arc plasma deposition method. Issue 7 (4th May 2020) - Hara, Takeshi; Hashiguchi, Hiroki; Ogishima, Masumi; Fujimoto, Daisuke; Yoshitake, Tsuyoshi
Abstract : In this study, we applied coaxial arc plasma deposition in vacuum and without substrate heating to prepare composite films of boron‐doped nanocrystalline diamond and amorphous carbon (B‐doped NCD/a‐C) exhibiting electrochemical characteristics similar to those exhibited by the conductive polycrystalline diamond electrodes. Furthermore, we confirmed that the deposited films can be used to determine the current density owing to various concentrations of potassium ferricyanide (K3 [Fe(CN6 )]). Moreover, the concentration of K3 [Fe(CN6 )] and its current density were strongly correlated. Based on these experimental results, the deposited films were highly valuable as electrodes for electrochemical sensors. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.